The role of communities in mental Hhalth care in low- and middle-income countries: a meta-review of components and competencies - Kohrt, Brandon A.; Asher, Laura; Bhardwaj, Anvita; Fazel, Mina; Jordans, Mark J.D.; Mutamba, Byamah B.; Nadkarni, Abhijit; Pedersen, Gloria A.; Singla, Daisy R.; Patel, Vikram (MDPI, 2018)
Community-based mental health services are emphasized in the World Health Organization’s Mental Health Action Plan, the World Bank’s Disease Control Priorities, and the Action Plan of the World Psychiatric Association. There is increasing evidence for effectiveness of mental health interventions delivered by non-specialists in community platforms in low- and middle-income countries (LMIC). However, the role of community components has yet to be summarized. Our objective was to map community interventions in LMIC, identify competencies for community-based providers, and highlight research gaps. Using a review-of-reviews strategy, we identified 23 reviews for the narrative synthesis. Motivations to employ community components included greater accessibility and acceptability compared to healthcare facilities, greater clinical effectiveness through ongoing contact and use of trusted local providers, family involvement, and economic benefits. Locations included homes, schools, and refugee camps, as well as technology-aided delivery. Activities included awareness raising, psychoeducation, skills training, rehabilitation, and psychological treatments. There was substantial variation in the degree to which community components were integrated with primary care services. Addressing gaps in current practice will require assuring collaboration with service users, utilizing implementation science methods, creating tools to facilitate community services and evaluate competencies of providers, and developing standardized reporting for community-based programs.